MENINGKATKAN DAYA KRITIS SANTRI MELALUI FORUM BAHTSUL MASA’IL DI PONDOK PESANTREN RAUDLATUL ULUM 1 PUTRA - Mohamad Alfin Zaironi; Pramesti Retno Suryaningtyas (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
Islamic boarding schools (pesantren) play a strategic role in shaping a generation that is knowledgeable, moral, and critical in facing the challenges of the times. However, memorization-based learning patterns often limit students' critical thinking. The Bahtsul Masa'il Forum exists as a scientific tradition that hones analytical, argumentative, and problem-solving skills through discussions of Islamic law based on classical texts. This study aims to analyze the role of the Bahtsul Masa'il Forum at the Raudlatul Ulum 1 Putra Islamic Boarding School in enhancing students' critical thinking. The method used is a qualitative descriptive case study, through observation, interviews, and documentation, analyzed using the Miles and Huberman model. The results show that this forum is effective in fostering skills in problem analysis, interpretation of classical texts, logistical argumentation, courage to express opinions, and independent research. This success is supported by the competence of the ustadz, scientific traditions, literature, and the enthusiasm of the students, although there are still obstacles such as limited time, differences in ability, and limited facilities.